Targeting non-alcoholic fatty liver disease: Design, X-ray co-crystal structure and synthesis of 'first-in-kind' inhibitors of serine/threonine kinase25. (1st November 2022) - Kiyeleko, Scarlett; Hocine, Sofiane; Mautino, Giséle; Kuenemann, Mélaine; Nawrotek, Agata; Miallau, Linda; Vuillard, Laurent-Michel; Mirguet, Olivier; Kotschy, Andras; Hanessian, Stephen
Graphical abstract: Abstract: We describe the synthesis of a series of 3- t -butyl 5-aminopyrazole p-substituted arylamides as inhibitors of serine-threonine25 (STK25), an enzyme implicated in the progression of non-alcoholic fatty liver disease (NAFLD). Appending a p- N -pyrrolidinosulphonamide group to the arylamide group led to a 'first-in kind' inhibitor with IC50  = 228 nM. A co-crystal structure with STK 25 revealed productive interactions which were also reproduced using molecular docking. A new series of triazolo dihydro oxazine carboxamides of 3- t -butyl 5-aminopyrazole was not active against STK25.